Thermal Ablation of Extended Liver Cancers: Assessment of Two New Bipolar Needle Electrodes. (September 2013) - Izzo, F.; Albino, V.; Palaia, R.; Piccirillo, M.; Nasto, A.; Carbone, G.; Capano, R.; Tatangelo, F.; Granata, V.
In the United States, approximately 155, 000 new cases of cancer of the liver and bile duct occur annually. Surgical resection of these tumors is considered the only treatment modality with a curative effect, but only 10% to 15% of patients with liver tumors are considered candidates for surgical resection. For this reason, several alternative treatment modalities have been developed. Radiofrequency energy has been the focus of increasing research and practice over the past few years. Recently, needle electrodes that encompass larger tissue volumes and radiofrequency generators that provide the increased power levels needed to heat these larger tissue volumes have become available. For this pilot study, we were interested in the evaluation of the capacity of larger sized needle electrodes to induce a predictable zone of tissue necrosis within diseased human liver. Furthermore, we wanted to prove safety and effectiveness of radiofrequency ablation in large sized liver tumors. In summary, the use of a bipolar 6 or 8 array electrode and power up to 180–220 watts energy was shown to produce controlled coagulation necrosis of targeted liver parenchyma and tumor with no observed complications.